The impact of virtual reality on manual dexterity of Parkinson's disease subjects: a systematic review. - Lahude, Arthur Both; Souza Corrêa, Philipe; P. Cabeleira, Maria Eduarda; Cechetti, Fernanda (Disability & Rehabilitation: Assistive Technology, 2023)
To present the latest available evidence on the effects of a VR-based therapy on the manual dexterity of PD subjects. The search was conducted in PubMed, EMBASE, and PEDro databases. Were included in the systematic review Randomized Clinical Trials, Pilot and Feasibility studies published up to December 2020. The studies should include at least one of the following assessments: Box and Blocks Test, 9-Hole Peg Test; Purdue Pegboard Test. PEDro Scale was used to assess the methodological quality of the included studies. Eight studies were included in the review. Most studies have shown an improvement in outcomes for manual dexterity, but most of them presented a high risk of bias with low methodological quality. A high heterogeneity was observed in the protocols used for each study. The results suggest that VR-based therapy has great potential and feasibility to be used as a manual dexterity rehabilitation protocol in PD subjects. However, these results must be interpreted carefully and studies with greater methodological rigor must be conducted. Rehabilitation programs using virtual reality seem to have greater adherence to the user. Immersive virtual reality systems seem to do better in manual dexterity than non-immersive systems. It is plausible to use virtual reality systems in telerehabilitation for manual dexterity training in subjects with Parkinson's' Disease. The use of Virtual Reality by the therapist in a rehabilitation program allows him to modulate the exercises, enabling a wide variety of therapeutic options.